2008
DOI: 10.1128/mcb.00726-08
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Specific mRNA Processing Targets for the Major Human hnRNP Proteins

Abstract: Alternative splicing is a key mechanism regulating gene expression, and it is often used to produce antagonistic activities particularly in apoptotic genes. Heterogeneous nuclear ribonucleoparticle (hnRNP) proteins form a family of RNA-binding proteins that coat nascent pre-mRNAs. Many but not all major hnRNP proteins have been shown to participate in splicing control. The range and specificity of hnRNP protein action remain poorly documented, even for those affecting splice site selection. We used RNA interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 64 publications
8
147
0
4
Order By: Relevance
“…RNA splicing requires a complex interplay of multiple RNA-binding proteins that are equipped with domains to bind sequence motifs on single stranded RNA to ensure accurate determination of exon recognition. In silico interrogation of the wild-type pre-mRNA segment derived from the 132-bp mutation-rich intronic sequence between exons 12 and 13 for accessible splicing factor binding sites resulted in identification of multiple potential binding sites for the RNA-binding proteins hnRNP-E2/ PCBP, hnRNP-I/PTB, and hnRNP-L, three members of the heterogenous nuclear ribonucleoprotein family of splicing factors that act as global regulators of alternative splicing and are abundantly expressed in infant leukemias (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) (Fig. 2A.1).…”
Section: Resultsmentioning
confidence: 99%
“…RNA splicing requires a complex interplay of multiple RNA-binding proteins that are equipped with domains to bind sequence motifs on single stranded RNA to ensure accurate determination of exon recognition. In silico interrogation of the wild-type pre-mRNA segment derived from the 132-bp mutation-rich intronic sequence between exons 12 and 13 for accessible splicing factor binding sites resulted in identification of multiple potential binding sites for the RNA-binding proteins hnRNP-E2/ PCBP, hnRNP-I/PTB, and hnRNP-L, three members of the heterogenous nuclear ribonucleoprotein family of splicing factors that act as global regulators of alternative splicing and are abundantly expressed in infant leukemias (40)(41)(42)(43)(44)(45)(46)(47)(48)(49) (Fig. 2A.1).…”
Section: Resultsmentioning
confidence: 99%
“…hnRNP A1 bound to ISS sequences can also promote exon exclusion, possibly through a mechanism that involves self-interaction of A1 molecules bound to distal sites and loop formation (Blanchette and Chabot 1999;Kashima et al 2007). While best characterized as repressors of splicing, hnRNP A/B proteins can also activate inclusion of some exons (Martinez-Contreras et al 2006;Venables et al 2008). As observed in PKM splicing regulation , hnRNP A1 and A2 frequently function redundantly in splicing regulation (Kashima and Manley 2003;Licatalosi and Darnell 2010).…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…As observed in PKM splicing regulation , hnRNP A1 and A2 frequently function redundantly in splicing regulation (Kashima and Manley 2003;Licatalosi and Darnell 2010). However, a genome-wide approach indicated that hnRNP A1/A2 targets may, in fact, be quite divergent (Venables et al 2008). Additional investigation is required to establish the extent of their redundancy, and whether any redundancy exists with a third family member, hnRNP A3, which shares more identity with hnRNP A1 than A2 does.…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…It is worth noting that 427 alternative splicing can be regulated by hnRNP proteins binding exonic splicing silencer 428 elements, thus excluding exons from mature mRNA. One study has found that hnRNP K may 429 play a prominent role in alternative splicing control because nearly half of 56 alternative splicing 430 events in apoptotic genes were affected upon hnRNP K depletion, either enhancing or 431 suppressing exon inclusion [57]. In support of our finding, it has been shown that hnRNP K 432 represses the production of the pro-apoptotic Bcl-x S spliced isoform, whereas its down-regulation 433 enhances the splicing of Bcl-x L to Bcl-x S [58].…”
Section: Discussion 375mentioning
confidence: 99%